Anthropogenic impact on erosion, pedogenesis and fluvial processes in the central European landscapes of the eastern Harz mountains forelands (Germany) - Stefan Dreibrodt; Carolin C.M. Langan; Markus Fuchs; Hans-Rudolf Bork (Quaternary Science Reviews, 2023)

Correction to: A local scale flood vulnerability assessment in the flood‑prone area of Khyber Pakhtunkhwa, Pakistan - Muhammad Nazeer; Hans‑Rudolf Bork (Natural Hazards, 2022)

A local scale flood vulnerability assessment in the flood-prone area of Khyber Pakhtunkhwa, Pakistan - Muhammad Nazeer; Hans-Rudolf Bork (Natural Hazards, 2021)
The central part of Khyber Pakhtunkhwa, Pakistan, is a highly flood-prone area of the province. The lives and assets of local communities are deeply vulnerable, attributed to the recurrence of seasonal floods. This concern has motivated decision-makers and the research community to develop and adopt best management practices to address flood vulnerability issues. One of the commonly used methods for evaluating flood vulnerability is empirical investigation using composite indicators. However, there are several issues with the available flood vulnerability literature, using composite indicators in the study area. The objectives of the current study are therefore twofold. On the one hand, it demonstrated in a comprehensive step-by-step approach to develop flood vulnerability composite indicator taking into account the broad range of stakeholders and the reliability of research. On the other hand, the flood vulnerability profile of the selected communities is being developed. Households’ survey was conducted in the selected communities using random sampling. The composite indicators of flood vulnerability were developed as the relative measure of flood vulnerability across the selected communities. A robustness check was also carried out using convenient techniques to address the problem of uncertainty. For such a purpose, the composite indicators of flood vulnerability were developed through various data rescaling, weighting, and aggregation schemes. The relative levels of flood vulnerability are identified across the selected communities, and the findings are illustrated by colored matrices. Different factors were identified for being responsible for the relative vulnerability of various communities. Jurisdiction-wise assessment of flood vulnerability reveals that communities located in Charsadda district are more vulnerable to flooding compared to those in Nowshera district. The study can facilitate a wide range of stakeholders and decision-makers not only to develop composite indicators for flood vulnerability but also to scientifically justify it as a management tool for flood risk reduction.

Indigenous resource management practices in the Gamo Highland of Ethiopia: challenges and prospects for sustainable resource management - Engdawork Assefa; Bork Hans-Rudolf (Sustainability Science, 2017)

Long-Term Indigenous Soil Conservation Technology in the Chencha Area, Southern Ethiopia: Origin, Characteristics, and Sustainability - Assefa Engdawork; Hans-Rudolf Bork (Ambio, 2014)

Deforestation and Forest Management in Southern Ethiopia: Investigations in the Chencha and Arbaminch Areas - Engdawork Assefa; Hans-Rudolf Bork (Environmental Management, 2014)

Soil degradation and agricultural sustainability: an overview from Iran - Iraj Emadodin; Daiju Narita; Hans Rudolf Bork (Environment, Development and Sustainability, 2012)

Geographie und Naturschutz?politisches Handlungsfeld mit rumlichen Implikationen - Karl-Heinz Erdmann; Hans-Rudolf Bork (Standort, 2004)